¿Es importante perder peso en tiempos de covid-19? (2021)
Obesity is a disease that leads to dysfunction of many organs. High adipose content leads to a chronic inflammatory condition and sufficient reserves for adipocyte hypertrophy. If the effect of COVID-19 is combined with obesity its severity increases. Both results combined are extremely dangerous and decrease life expectancy. Even the care of people with obesity in hospitals is affected, making their care more difficult and requiring more staff. The mechanical ventilation needs of people with obesity are predictably increased and this can be crucial, as not all hospitals have this equipment. Therefore, exercising by combining strength and endurance training is another reason these days to fight the virus. Adding caloric restriction is also another key factor to achieve significant effects.